The impact of mental health literacy on depression, anxiety and well-being among vocational nursing students: mediating roles of resilience - Yang, Yanying; Miao, Lihong; Liu, Xuejuan; Su, Weicai; Liu, Sujiao (Frontiers in Psychiatry, 2025)
BackgroundAnxiety and depression are increasingly prevalent among nursing students. Mental Health Literacy (MHL) has been regarded as a potential protective factor for mental health. However, the relationship between MHL, resilience, anxiety/depression and well-being among nursing students is still understudied.ObjectiveThis study aimed to explore the relationship between MHL and anxiety, depression and well-being, as well as the mediating role of resilience among nursing students.MethodsWe adopted a cross-sectional online questionnaire approach using the “Questionnaire Star” platform. The Mental Health Literacy Questionnaire-short Version for Adults (MHLq-SVa), Connor-Davidson Resilience Scale-10 (CD-RISC-10), The World Health Organization-Five Well-Being Index (WHO-5), Generalized Anxiety Disorder-7 (GAD-7), and Patient Health Questionnaire (PHQ-9) were used to measure the MHL, resilience, well-being and anxiety/depression. Descriptive statistics, Pearson correlation analysis and mediation effect analysis were conducted.ResultsThe prevalence of anxiety and depression among nursing students were 39.4% and 9.3% respectively. MHL was negatively correlated with anxiety (r = -0.19, p < 0.001) and depression (r = -0.20, p < 0.001). MHL was positively correlated with resilience (r = 0.43, p < 0.001) and well-being (r = 0.06, p < 0.001). Resilience partially mediated the relationship between MHL and anxiety (indirect effect = -0.040; 95%CI: -0.053 to -0.030), the relationship between MHL and depression (indirect effect = -0.057; 95%CI: -0.073 to -0.040), and the relationship between MHL and well-being (indirect effect = 0.203; 95%CI: 0.177 to 0.228).ConclusionHigher MHL levels among nursing students is associated with stronger resilience, further associated with lower levels of anxiety/depression and higher levels of well-being. Our findings provide important guidance for educational administrators and helps them formulate targeted strategies to prevent anxiety/depression among nursing students.